2017
DOI: 10.1002/poc.3689
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐2‐Aminocyclohexanol derivatives as pH‐triggered conformational switches

Abstract: A series of trans-2-aminocyclohexanol derivatives have been explored as powerful conformational pH triggers. On protonation of the amino group, a conformer with equatorial position of ammonio and hydroxy groups becomes predominant because of an intramolecular hydrogen bond and electrostatic interactions. The energy of these interactions was estimated to be above 10 kJ/mol and in some models exceeded 20 kJ/mol (strong enough to twist a ring in tert-butyl derivatives). As a result of this conformational flip, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…The model compounds 3a ‐ c containing ethoxycarbonyl groups, the aminosulfanyl and hydroxyl substituents, and 5a ‐ c containing only the aminosulfanyl and hydroxyl substituents were synthesized by opening epoxides 2 and 4 under basic conditions with sodium tetraborate as a catalyst according to Scheme . Similar to previous studies, the diastereomers 3 with the required configuration were the only isolable products. Compounds 8c,f,k and 9c,f,k with a bulky tert ‐butyl conformational anchor were also synthesized to be used as standards due to their conformational bias (Scheme ).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The model compounds 3a ‐ c containing ethoxycarbonyl groups, the aminosulfanyl and hydroxyl substituents, and 5a ‐ c containing only the aminosulfanyl and hydroxyl substituents were synthesized by opening epoxides 2 and 4 under basic conditions with sodium tetraborate as a catalyst according to Scheme . Similar to previous studies, the diastereomers 3 with the required configuration were the only isolable products. Compounds 8c,f,k and 9c,f,k with a bulky tert ‐butyl conformational anchor were also synthesized to be used as standards due to their conformational bias (Scheme ).…”
Section: Resultsmentioning
confidence: 89%
“…They play a central role in a design of controllable compounds, molecular machinery, and intelligent materials with a variety of possible applications including drug release, new sensor techniques, or information storage and transmission . The cyclohexane‐based molecular systems provide an efficient prototype for such switches . Particularly, the trans ‐2‐aminocyclohexanol moiety (Scheme ) was used to construct the crown‐ethers and podands with the pH‐triggered conformations and the pH‐sensitive “flipids” for “fliposomes.” Protonation of the amino group in these compounds causes a strong intramolecular hydrogen bond HO⋯H–N + (in B H + in Scheme ), which stabilizes the originally unstable form B , where the bulky ester groups on the opposite end of the cyclohexane are spread into axial positions (“peacock effect”).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreasedr elease (< 30 %) was observed with the corresponding cis isomer.I na ddition, cryo-EM studies showed considerable membrane defects and budding at lower pH. In work since this initial report, the basicity of the amine group has been varied, [10] the mechanistic details of release have been further studied, [11] incorporation into liposomes hasbeen shown to enhance gene delivery, [12] libraries of compounds with different properties have been studied and compared, [13] and this system has been combined with spherical polycationic brushes for pH-driven releasefrom these nanoparticles. [14] LeBlond and co-workersh ave investigated pH-responsive lipid switchesb ased on ad i(methoxyphenyl)pyridine scaffold.…”
Section: Ph-responsive Lipid Switchesmentioning
confidence: 99%